(untitled) (Biological Sciences - PJSIR, 1999)
Seed cotton yield, ginning out turn percentage and fibre length data fromsix locations in Multan Zone were evaluated for stability. All these cultivars understudy were stable for ginning out turn percentage in these environments. S-12, MNH93 and B557 were identified as the most stable for yield performance. Utilisation of MNH321 was recommended in hybridization to have better stability for ginning out turn percentage. S-12 was identified to be the most stable for staple length. In conclusion for better stability in yield of seed cotton, ginning out turn percentage and staple length, utilisation of MNH93, B557, MNH321 and S-12 in the breeding programmes are recommended.